Ethical Contracts vs. Commercial Realities in Indonesian Sharia Insurance - Istianah Zainal Asyiqin (Fiat Justisia)
This article examined legal issues within Indonesia's Sharia insurance industry, focusing on implementing dual contracts combining tabarru’ (voluntary) and tijarah (business) agreements. The qualitative study used secondary data and a taxonomic technique to identify legal challenges. Ideally, the contract structure should separate the management of these two agreements, with tabarru’ as the primary contract and tijarah as supplementary. However, the findings revealed that Indonesia's takaful industry prioritized the supplementary tijarah contract over the primary tabarru’. This issue resulted in inadequate separation of tabarru’ and tijarah funds, leading to the mixing of returns from both sectors. This practice contradicted the fatwas issued by the National Sharia Council-The Indonesian Ulama Council (DSN-MUI) regarding Islamic insurance.Additionally, the article identifies ambiguities within some DSN-MUI guidelines. To address these issues, the article proposed an alternative contract scheme from the perspective of fiqh al-mu'amalah (Islamic economic law), suggesting that tabarru’ could be based on a fee (ujrah). In contrast, other contracts could be structured around profit and loss-sharing investment agreements.